A coding variant in TMC8 (EVER2) is associated with high risk HPV infection and head and neck cancer risk. - Caihua Liang; Karl T Kelsey; Michael D McClean; Brock C Christensen; Carmen J Marsit; Margaret R Karagas; Tim Waterboer; Michael Pawlita; Heather H Nelson (PLoS ONE, 2015)
HPV infection is a causal agent in many epithelial cancers, yet our understanding of genetic susceptibility to HPV infection and resultant cancer risk is limited. Epidermodysplasia Verruciformis is a rare condition of extreme susceptibility to cutaneous HPV infection primarily attributable to mutations in TMC6 and TMC8. Genetic variation in the TMC6/TMC8 region has been linked to beta-type HPV infection and squamous cell carcinoma of the skin, cervical cancer, HPV persistence and progression to cervical cancer. Here, we have tested the hypothesis that the common TMC8 SNP rs7208422 is associated with high-risk HPV infection and risk of head and neck squamous cell carcinoma (HNSCC). Seropositivity to the HPV L1 protein (HPV16, 18, 11, 31, 33, 35, 45, 52, 58) was measured in 514 cases and 452 population-based controls. Genotype was significantly associated with seropositivity to HPV18 L1 (OR TT vs AA = 0.48, 95% CI = 0.22-0.99) and borderline significantly associated with HPV16 L1 (OR TT vs AA = 0.58, 95% CI = 0.22-1.17). There was a consistent inverse association between TMC8 genotype and infection with other HPV types, including statistically significant associations for HPV31 and HPV52. Consistent with these results, the variant T genotype was associated with a reduced risk of HNSCC (ORAT: 0.63, 95% CI 0.45-0.89, ORTT: 0.54, 95% CI 0.36-0.81), even among subjects seronegative for all HPV types (ORAT: 0.71, 95% CI 0.45-1.11, ORTT: 0.54, 95% CI 0.31-0.93). Our data indicate that common genetic variation in TMC8 is associated with high-risk HPV infection and HNSCC etiology.